Case Report: Metastatic Parosteal Osteosarcoma in a Dog - Samuels, Sarah K.; Cook, Matthew R.; Green, Eric; Jennings, Ryan; Pool, Roy R.; Wavreille, Vincent A.; Kisseberth, William C.; Selmic, Laura E. (Frontiers in Veterinary Science, 2021)
This case report describes a rare form of malignant bone tumor in an 8-year-old Labrador retriever. This dog initially presented for evaluation of a right distal humeral mass. Radiographs of the right elbow and thorax were performed, revealing a smooth mineralized mass adjacent to the lateral aspect of the distal humerus and a 5mm pulmonary nodule. Computed tomography (CT) of the humerus and thorax showed a smooth mineralized lesion adjacent to the lateral humeral epicondyle, and a right cranial lung lobe nodule with a thin mineral rim. Surgical biopsies of both lesions were diagnostic for parosteal osteosarcoma (POSA). The dog was then treated with stereotactic body radiation therapy (SBRT) which controlled the dog’s discomfort for 14 months until he became progressively painful and subsequently had his right forelimb amputated. This case report is the first to document the CT imaging characteristics of a metastatic appendicular POSA in a dog and the first dog described with POSA treated with SBRT. The dog lived for 849 days after initial presentation with pulmonary metastatic disease.